Intravenous administration of viral vectors expressing prostate cancer antigens enhances the magnitude and functionality of CD8+ T cell responses. Issue 11 (2nd November 2022) - Vardeu, Antonella; Davis, Charlotte; McDonald, Ian; Stahlberg, Guilherme; Thapa, Barsha; Piotrowska, Kinga; Marshall, Margaret A; Evans, Thomas; Wheeler, Vicky; Sebastian, Sarah; Anderson, Katie
Abstract : Background: The use of immunotherapeutic vaccination in prostate cancer is a promising approach that likely requires the induction of functional, cytotoxic T cells . The experimental approach described here uses a well-studied adenovirus-poxvirus heterologous prime-boost regimen, in which the vectors encode a combination of prostate cancer antigens, with the booster dose delivered by either the intravenous or intramuscular (IM) route. This prime-boost regimen was investigated for antigen-specific CD8+ T cell induction. Methods: The coding sequences for four antigens expressed in prostate cancer, 5T4, PSA, PAP, and STEAP1, were inserted into replication-incompetent chimpanzee adenovirus Oxford 1 (ChAdOx1) and into replication-deficient modified vaccinia Ankara (MVA). In four strains of mice, ChAdOx1 prime was delivered intramuscularly, with an MVA boost delivered by either IM or intravenous routes. Immune responses were measured in splenocytes using ELISpot, multiparameter flow cytometry, and a targeted in vivo killing assay. Results: The prime-boost regimen was highly immunogenic, with intravenous administration of the boost resulting in a sixfold increase in the magnitude of antigen-specific T cells induced and increased in vivo killing relative to the intramuscular boosting route. Prostate-specific antigen (PSA)-specific responses were dominant in all mouse strains studied (C57BL/6, BALBc, CD-1 and HLA-A2 transgenic). Conclusion: This quadrivalent immunotherapeutic approach using four antigens expressed in prostate cancer induced high magnitude, functional CD8+ T cells in murine models. The data suggest that comparing the intravenous versus intramuscular boosting routes is worthy of investigation in humans.